Assessing hormonal contraceptive dispensing and counseling provided by community pharmacists in the United Arab Emirates: a simulated patient study - Mobark DM; Al-Tabakha MM; Hasan S (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Hormonal contraceptive pills have evolved as a common form of contraception worldwide. Pharmacists play a vital role in providing safe and effective access to these medicines. In many developing countries such as the United Arab Emirates (UAE), these medicines are available to the general public without the presentation of a prescription which requires the pharmacist to shoulder responsibility by assessing and educating patients to assure their appropriate use. Objectives: To evaluate community pharmacists' current practice of dispensing and counseling on hormonal contraceptives Methods: Simulated patient methodology was used in this study. A single simulated patient visited community pharmacies requesting an oral contraceptive as per a preplanned scenario. Information from the visits were recorded on a data collection form including: pharmacist assessing patient eligibility to take hormonal contraceptives, selecting the appropriate oral contraceptive, providing complete counseling on how to use the pill, adherence, missed dose handlings and side effects of the medication. The Pharmacist was prompted by the simulated patient to provide the information if they did not provide spontaneous counseling. The quality of pharmacists' counseling was rated and consequently coded as complete, incomplete or poor. Results: A total of 201 community pharmacies were visited. More than 92% of the pharmacists did not ask the simulated patient any question to assess their eligibility to use contraceptives. Twenty three pharmacists (11.4%) selected the proper product. One hundred seventeen (58.2%) of the pharmacists provided spontaneous counseling on how to use the pill, 17 of them had their counsel rated as complete, but none of the pharmacists provided spontaneous counseling regarding adherence or side effects of the medications. On prompting, 10 pharmacists (12%) provided complete counseling regarding how to use oral contraceptives, 14 pharmacists (7.0%) provided complete counseling on adherence and missing dose handling and five pharmacists (2.5%) provided complete counseling about expected side effects. Conclusions: Pharmacists' practice regarding hormonal contraceptive dispensing and counseling was suboptimal in this study. Areas needing intervention were related to pharmacist assessment of eligibility for oral contraceptive use, choice of optimal oral contraceptive for patient-specific co-morbidities and provision of adequate counseling regarding proper use, adherence and missed dose handlings.